1991
DOI: 10.1177/002076409103700306
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Chinese and American Male Students towards Mental Illness

Abstract: Attitudes towards mental illness were measured by the Opinion About Mental Illness Scale (OMI) for 83 male graduate college students from American and Chinese cultural backgrounds. The OMI questionnaire consisted of five factors: A) Authoritarianism, B) Benevolence, C) Mental Hygiene Ideology, D) Social Restrictiveness, and E) Interpersonal Etiology. Statistically significant differences between the two groups of subjects on Factors A, B, D and E of the OMI were found. American students performed lower on "Aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…Supporting past work comparing mental illness stigma among Chinese vs. Western groups (Shokoohi-Yekta & Retish, 1991; Furnham & Wong, 2007), Study 1 indicated increased levels of stigma (i.e., social restriction and intimate social distance) and perception of threat (i.e., symbolic, tangible, and threat of genetic contamination) among Chinese groups. Our results extend prior studies showing independent pathways for symbolic and tangible threats in predicting stigma by identifying and examining the effects of a ‘culture-specific’ source of threat (Crandall & Moriarty, 2011; Corrigan et al, 2005).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Supporting past work comparing mental illness stigma among Chinese vs. Western groups (Shokoohi-Yekta & Retish, 1991; Furnham & Wong, 2007), Study 1 indicated increased levels of stigma (i.e., social restriction and intimate social distance) and perception of threat (i.e., symbolic, tangible, and threat of genetic contamination) among Chinese groups. Our results extend prior studies showing independent pathways for symbolic and tangible threats in predicting stigma by identifying and examining the effects of a ‘culture-specific’ source of threat (Crandall & Moriarty, 2011; Corrigan et al, 2005).…”
Section: Discussionsupporting
confidence: 58%
“…Per prior studies (Shookohi-Yekta & Retish, 1991; Furnham & Wong, 2007), Chinese-Americans evidenced more socially restrictive attitudes. Further, there was partial support for hypothesized differences in intimate social distance as Chinese–Americans endorsed more intimate social distance towards the sibling of a person with mental illness.…”
Section: Discussionmentioning
confidence: 64%
“…Generally, public attitude toward mental illness may be mediated by various factors consisted of demographic variables, socio-cultural factors, familiarity with mental illness, and sources of publicity [1, 2, 10-13]. Specifically, several factors may influence medical students’ attitude toward mental illness such as teaching methods, educational atmosphere, medical training environment, role models, and direct patient care, as well [13-21].…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies have indicated that respondents from Chinese groups endorse significantly greater negative stereotypes (e.g., unpredictability [6]) and pejorative attitudes (e.g., greater authoritarianism and social restrictiveness [7]) towards people with mental illness when compared with their Western counterparts [8–10]. Such negative attitudes give rise to discrimination that is commonly experienced by people with schizophrenia in China when their illness status is revealed [1].…”
Section: Introductionmentioning
confidence: 99%